Communicative Language Teaching Approach Potential for English Language Teaching - Kurniawan, Agung Budi; ., Sumani (KnE Social Sciences, 2022)
Communicative language teaching or CLT has some potential benefits to be applied for English language teaching or ELT. This article reviews some previous studies about the potential based on library study. The potential could be gained for the scope of material, pedagogic process, and teachers’ and students’ competence. The materials could be extended as large as possible, but it is still limited for proper issues. Materials based on real-life or daily life contexts are recommended to be applied, and artificial materials should be avoided. The pedagogic process could be improved because the communicative approach brings social skills for students. It could be applied to both young and adult learners. English teachers could also develop their skills as managers of classroom interaction. Moreover, students could gain communicative competence for social purposes because it is the main purpose of CLT. CLT is an approach that does not provide a specific method. Teachers must decide appropriate single or combination of methods to gain communicative competence for the field application. The main conclusion is that CLT is recommended for a language teaching program whose purpose is to give communicative competence. Keywords: communicative, English, teaching, approach